The Gold Hunters: A Story of Life and Adventure in the Hudson Bay Wilds - Curwood, James Oliver, 1878-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Gold Hunters: A Story of Life and Adventure in the Hudson Bay Wilds" by James Oliver Curwood is a novel written in the early 20th century. The story revolves around the thrilling adventures of Roderick Drew, Wabigoon, and the faithful Mukoki as they venture into the wilderness of Canada on a quest for gold, all while facing numerous challenges and dangers, including the ruthless Woongas, a tribe of outlaw Indians. At the start of the narrative, the scene is set in the vast solitude of the Canadian wilderness, where the protagonists are on a high-stakes pursuit of a Hudson Bay mail sled. They encounter various elements of nature and wildlife as they track the sled, seeking adventure and facing the harsh realities of the wild. Wabigoon, whose sister Minnetaki has been captured, and Mukoki, an experienced Indian warrior, exemplify bravery and loyalty throughout their desperate chase. The opening lays the groundwork for a gripping tale filled with excitement, tension, and the intrinsic bond of friendship, setting the stage for the challenges that lie ahead as they embark on their quest to rescue Minnetaki and find the fabled gold. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Roger Frank and Sue Clark, Suzanne Shell, Björn Lijnema and PG Distributed Proofreaders
Keywords: Gold mines and mining -- Fiction; Hudson Bay -- Fiction